Silek Pangian in the Bolek Laman Tuo Tradition in The Social Structure of The Nagari Sungai Dareh Community, Dharmasraya District, West Sumatra Province - Malindo, Ihsanul Malindo; Wilma Sriwulan (Kirana Publisher (KNPub), 2024)
This research, entitled